The impact of COVID-19 pandemic on online learning: the role of conceptual motivation models and the urgency on students sustainable wellbeing (case study on higher education students in DKI Jakarta) / Rifqi Alif Nugraha and Paulina - Nugraha, Rifqi Alif; Paulina, Paulina (UiTM Cawangan Johor, 2023)
This study aims to examine the Impact of Covid-19 Pandemic on Online Learning: The Role of Conceptual Motivation Models and The Urgency on Students Sustainable Wellbeing with the variables Self-Determination, Self- Efficacy, Self-Regulation, Digital Literacy, Family Support, University Support, Emotional Engagement, and Students Sustainable Wellbeing. This research was conducted on university students in DKI Jakarta. The sample in this study consisted of143 respondents. The analytical method used is Structural Equation Modeling (SEM). The results of the analysis show that digital literacy and emotional engagement have an influence on students' sustainable wellbeing. Meanwhile, self- determination, self-efficacy, self-regulation, family support, and university support have no effect on students' sustainable wellbeing. Keywords: Self-Determination, Self-Efficacy, Self-Regulation, Digital Literacy, Family Support, University Support, Emotional Engagement, Students Sustainable Wellbeing.